COOP AND COHP BONDING-ANTIBONDING IN THE PLANE SUPERCONDUCTING YBa2Cu3O7 - Flores R., Luis (2007)
Using the base "Augmented Spherical Waves (ASW)" the quantities are calculated and discuss "Orbital Crystal Overlap Population (COOP)" and "Orbital Crystal Hamiltonian Population (COHP)" that give information about the formation of states bonding and antibond1ng and consequently on the stability in the system YBa2Cu3O7. The calculation realizes in the reg1on of the crystalline cell that it shows superconductivity. There is demonstrated that in the region is highly unstable in the state not superconductor with a great quantity of states antibonding lor below and in the energy of Fermi E(F). This situation can induce a transit1on of local phase to the state superconductor.